(untitled) (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
THE IMPACT OF STUNTING MALNUTRITION OF ORODENTAL HEALTH IN CHILDREN: A SCOOPING REVIEW I Gusti Ayu Ari Agung, Dewa Made Wedagama, I Gusti Ayu Agung Hartini, Ni Putu Widani Astuti, I Nyoman Panji Triadnya Palgunadi, Gusti Ayu Yohanna Lily, Ni Putu Idaryati, Ilma Yudistian 74-79 PERIODONTICS IN ARTIFICIAL INTELLIGENCE ERA : A LITERATURE REVIEW Ni Wayan Arni Sardi, Ni Luh Putu Sri Maryuni Adnyasari, Made Talitha Suryaningsih Pinati 80-85 REGENERATIVE TREATMENT USING PERIODONTAL FLAP SURGERY COMBINED Ti-OSS®, PERICARDIUM MEMBRANE AND PLATELET-RICH FIBRIN IN CHRONIC PERIODONTITIS Abyan Teguh Saputro, Vincensia Maria Karina 86-93 MINIMAL INVASIVE FOR MAXIMAL RECOVERY IN DENTAL TRAUMA : A CASE REPORT Anak Agung Manik Swayoga, Ilma Yudistian 94-100 AESTHETIC IMPROVEMENT IN ONE VISIT PERIODONTAL PLASTIC SURGERY USING SCALPEL AND LASER SURGICAL TECHNIQUE (CASE REPORT) Nabilah, Vincensia Marina Karina 101-108 TELEDENTISTRY IN A JURIDICAL PERSPECTIVE: CRIMINAL, CIVIL AND ADMINISTRATIVE ASPECTS Nyoman Ayu Anggayanti, Ida Bagus Fajar Manuaba, I Gusti Agung Gede Utara Hartawan 109-114 THE EFFECTIVENESS OF ORANGE PEEL EXTRACT TOOTHPASTE IN LIGHTENING TEETH AND PREVENTING BACTERIAL INFECTIONS LEADS TO HALITOSIS Dentino Asmara Putra, Ni Nengah Aderinaarta Pramudani, Armyawati, Wiwekowati 115-120 CASE MANAGEMENT OF ANTERIOR TOOTH INTRUSION DUE TO TRAUMA Aryo Sutowijoyo, Prima Nerito 121-126 TRAINING OF TRAINERS METHOD FOR ELEMENTARY SCHOOL TEACHERS TO IMPROVE DENTAL HEALTH KNOWLEDGE Yudha Rahina, I Gusti Agung Ayu Chandra Iswari Dewi, I Gusti Ayu Ratih Pramesti, Pudak Elang, Eko Sri Yuni Astuti 127-131 FRENECTOMY ON MAXILLARY LABIAL FRENULUM PENETRATING PAPILLA TYPE BY CONVENTIONAL SURGICAL TECHNIQUES: A CASE REPORT Dwis Syahriel, Dwis Syahrul, Arya Kusuma Agraha, Asri Riany Putri 132-138 COST BENEFIT ANALYSIS OF OPENING DENTAL POLY SERVICES OR CHILDREN'S PHYSIOTHERAPY POLY SERVICES AT SAFAKILLAH CLINIC Prima Nerito, Aryo Sutowijoyo 139-147 NECROSIS FACTOR-ALPHA A POTENTIAL THERAPEUTIC TARGET FOR PERIODONTITIS AND DIABETES MELLITUS Angela Widjaja, Ahmad Syaify, Hendrawati 148-157 THE EFFECTIVENESS OF CEMCEM (Spondiaspinnata (L.f) Kurz) LEAF EXTRACT IN INHIBITING THE GROWTH OF Streptococcus mutans Putu Sulistiawati Dewi, I Made Merta Suparka 158-163 IDENTIFICATION AND TREATMENT OF ERYTHEMA MULTIFORME INDUCED BY ALLOPURINOL I Nyoman Gede Juwita Putra, Raziv Ganesha, I Gusti Ngurah Putra Dermawan 164-169 ACUTE TOXICITY TEST OF AMBON BANANA TREE SAP EXTRACT ON MICE (Mus Muculus L.) Setiawan, Hendri Poernomo, Reza Pramana 170-176 KNOWLEDGE LEVEL OF DENTAL STUDENTS FKG UNBRAH ABOUT THE TREATMENT OF STAINLESS-STEEL CROWN (SSC) IN PEDIATRIC PATIENTS AT DENTAL HOSPITAL BAITURRAHMAH Sri Pandu Pandu, Leny Sang Surya, Utami Arma, Resa Ferdina, Hanifah Maharani Al Asad 177-181 IMPLEMENTATION OF THE MOBILE-BASED DENTALK APPLICATION AS A MEDIA FOR INCREASING PUBLIC KNOWLEDGE IN USING THE TELEDENTISTRY APPLICATION Sari Aldilawati, Amanah Pertiwisari, Andi Muhammad Irfan M.Amir 182-186 ANTIBACTERIAL COMPARISON BETWEEN MANUKA HONEY AND TUALANG HONEY AGAINST PORPHYROMONAS GINGIVALIS BACTERIA. Veronica Septnina Primasari, Desy Fidyawati, Ike Nurmalisari Ramadhani 187-194 EFFECT OF KECEMCEM TREE (SPONDIAS PINNATA) BARK EXTRACT GEL TO INCREASE COLLAGEN POST WISTAR RATS CURETTAGE Eka Pramudita Ramadhany, Media Sukmalia Adibah, Astrid Rahayu Dewi 195-201 THE RELATIONSHIP BETWEEN STRESS DURING THE COVID-19 PANDEMIC AND THE INCIDENCE OF RECURRENT APHTHOUS STOMATITIS Afryla Femilian, Khulia Furaida, Afina Hasnasari Heningtyas 202-208 SPACE SEARCH FOR MINOR CROWDING CASES WITH EXPANSION PLATE IN PATIENTS WITH A HISTORY OF ANTIDEPRESSANT DRUG CONSUMPTION Puspitarini Nindya Wardana, Yely Okta Mariza 209-215 THE ROLE OF TRICHOMONAS TENAX IN PERIODONTAL DISEASE: A LITERATURE REVIEW Nadia Nabiilah Rahmah Rayugi, Emma Rachmawati, Ina Hendiani 216-221 DESCRIPTION OF PATIENTS WITH ODONTECTOMY IN RSUD SULTAN FATAH DEMAK Fuad Fatkhurrohman, Syarifah Nova Amiza Zam, Dea Hardyana Putri, Khairunnisa Pulungan, Isnadia Rachmah Ika 222-227 THE RELATIONSHIP OF CHEWING GUM WITH TEMPOROMANDIBULAR JOINT DISORDERS: RAPID REVIEW Evy Carolina Choandra, Rasmi Rikmasari, Seto Pramudita 228-236 INHIBITORY POWER OF MAS BANANA PEEL EXTRACT (MUSA ACUMINATA LADY FINGER) ON THE GROWTH OF STAPHYLOCOCCUS AUREUS IN VITRO Dwis Syahrul, Ni Putu Widani Astuti, Dwis Syahriel, Desak Putu Diah Pradnyani, M. Dian Firdausy 237-241